Impact of peginterferon alpha‐2b and entecavir hydrate combination therapy on persistent viral suppression in patients with chronic hepatitis B. Issue 6 (12th April 2013) - Hagiwara, Satoru; Kudo, Masatoshi; Osaki, Yukio; Matsuo, Hiroo; Inuzuka, Tadashi; Matsumoto, Akihiro; Tanaka, Eiji; Sakurai, Toshiharu; Ueshima, Kazuomi; Inoue, Tatsuo; Yada, Norihisa; Nishida, Naoshi
Abstract: The ideal approach to treat chronic hepatitis B remains controversial. This pilot study aimed to evaluate the effectiveness of peginterferon (PEG‐IFN) α‐2b and entecavir hydrate (ETV) as a combination therapy for patients with chronic hepatitis B, particularly in the context of virological response and the reduction of intrahepatic covalently closed circular DNA (cccDNA). A total of 17 patients with hepatitis B virus (HBV) genotype C were enrolled in this study. All subjects were treated with this combination therapy for 48 weeks and observed for an additional 24 weeks. All patients underwent liver biopsy before and after the therapy period. Changes in cccDNA levels and liver histology were monitored between biopsies. Among the 11 patients who exhibited pre‐therapy hepatitis B e antigen (HBeAg), 8 (73%) showed evidence of HBeAg seroconversion by the end of the follow‐up period. Serum HBV DNA levels decreased by 5.2 and 3.3 log copies/ml (mean) by the end of the therapy and follow‐up periods, respectively. In addition, intrahepatic cccDNA decreased significantly to 1.4 log copies/µg (mean) by the end of the therapy period. Among the 11 patients who did not experience viral relapse, only 2 (18%) exhibited high levels of cccDNA (>4.5 log copies/µg) by the end of the treatment period. In contrast, all relapsed subjects exhibited significantly higher levels of cccDNA than subjects who did not relapse ( P = 0.027). The combination regimen is a promising approach to treat chronic hepatitis B and may achieve significant reduction in serum HBV DNA and intrahepatic cccDNA. J. Med. Virol. 85: 987–995, 2013. © 2013 Wiley Periodicals, Inc.